RETRACTED: Using blast energy as an effective technology to provide subgrade stability in road construction - Gorodnova E.V.; Tcvetkov A.A. (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001